HUBUNGAN POLA ASUH ORANGTUA DENGAN KEMATANGAN EMOSI REMAJA DI SMK NEGERI 2 SEWON BANTUL YOGYAKARTA - Khoirul Azizah, Bety Agustina Rahayu (Jurnal Ilmiah Keperawatan, 2022)
Background : Adolescence is the peak point of emotionality, where there is emotional development, physical growth, especially the sexual organs that affect the development of new emotions or feelings and impulses experienced, such as feelings of love, longing, and the desire to get acquainted more intimately with the opposite sex. During this period of development, adolescents will be exposed to mental and emotional problems. Emotional mental health problems often occur in adolescence including psychosexual changes, peer influence, moral development disorders, stress in adolescence, high-risk behavior.Purpose : This study aims to determine "The relationship between parenting patterns and adolescent emotional maturity at SMK Negeri 2 Sewon Bantul Yogyakarta".Methods : This type of research is a quantitative non-experimental with a descriptive correlational research design, namely examining the relationship between variables. While the approach used is cross sectional.Results : Most of the parenting styles apply the democratic type of parenting, as many as 46 respondents (68%) with a moderate level of emotional maturity, namely 34 respondents (50%). Based on data analysis using Kendall Tau, the correlation value is 0.149 with a significance level of p> 0.05.Conclusion : There is no relationship between parenting style and adolescent emotional maturity at SMK Negeri 2 Sewon Bantul Yogyakarta.